Chromium (Cr) Metal Absorbtion Using Symbiosis of Fimbristylis globulosa with Agrobacterium sp. - Alfian Chrisna Aji; Novia Citra Paringsih; Dwi Rizaldi Hatmoko; Ilham Mujahidin; Riza Rifai; Afif Iqbal Alviandi; Almas Al Jinan; Mujahidin Mujahidin; Sofyan Anif (Bioeksperimen: Jurnal Penelitian Biologi, 2023)
Chromium (Cr) metal is a pollutant caused by industrial waste disposal and agricultural activities. An alternative solution to managing chromium pollution in an environmentally friendly manner is phytoremediation using Fimbristylis globulosa combined with Agrobacterium sp. This research aims to measure 1). the ability of Fimbristylis globulosa combined with Agrobacterium sp. to absorb Cr metal; and 2). the value of the Cr metal bioconcentration factor (BCF) absorbed by Fimbristylis globulosa combined with Agrobacterium sp. This research used factorial design 2x5 with randomized design. Chromium metal analysis using atomic absorption spectrophotometer. Data were analyzed using BCF test. The results showed: 1) the highest Cr metal absorption in the treatment of Fimbristylis globulosa-Agrobacterium sp.-Cr metal content of 30 ppm (T2V3) root: 7,987 ppm and shoot: 15,649 ppm; 2) the highest value of Cr metal BCF in the treatment of Fimbristylis globulosa-Agrobacterium sp.-Cr metal content of 30 ppm (T2V3) root is 0.266 and Fimbristylis globulosa-Agrobacterium sp.-Cr metal content 10 ppm (T2V1) shoot is 0.675. Conclusions of this research are: 1) Fimbristylis globulosa combined with Agrobacterium sp. has a higher Cr metal absorption ability than without a combination of both; and 2) Fimbristylis globulosa combined with Agrobacterium sp. has a higher value of the Cr metal BCF than without a combination of both.